(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: Dog bites are a public health and economic problem affecting mainly low and middle income countries including Iraq especially the central provinces of this country, epidemiologic studies to assess Knowledge. Attitudes and Practices of dog bite victims were not found in Iraq. Objective: To asses the knowledge, attitudes and practices among a sample of dog bite victims in Babylon province- Iraq during the year2017. Patients and Methods: A cross sectional study was conducted after obtaining the approval of health authorization on a convenient sample of dog bite injured patients attending the emergency department of Al Hilla teaching hospital during the period from 1st February to the beginning of June, 2017. A pre tested semi structured questionnaire was used to assess the knowledge, Attitudes and Practices of participants by face to face interview. Data were analyzed statistically using Statistical Package of Social Science version 22. Results: The mean age and the standard deviation of the 212 participants ages was 19.74 +14.68 years, male victims were significantly more predominate (66.5%) and younger than female victims p<0.05. Students constituted the majority of dog bite cases (44.8%). The study revealed that lower limbs were the most common bitted site (61.3%), bitten neck and trunk are significantly correlated with young age p<0.05.The majority of dog bites occurred during day time (63.7%) , less than one fifth of victims (17%) knew the cause and the way of transmission of rabies but 73.6% of them did not know the owners of dogs, about 90% of them witnessed free dogs around their homes, only 1.4% of the victims knew confirmed dead cases of human rabies in their place of residence, more than 90% of patients had positive attitude toward advising others to deal correctly with dog bite injuries and advised others to receive anti rabies vaccine immediately after exposure and 100% of them had received at least single prophylactic post exposure vaccine but only (20%) of victims washed their wounds by soap and water, unfortunately 3.3% had wash and sterile the wound while none of them attended lectures on dog bites first aids. Conclusion: This study showed that dog bites are prevalent in the province and rabies is endemic in Babylon province, there is a reasonable positive attitude towards dog bites but specific aspects of knowledge and practices regarding this health are poor.